Conceptual apparatus of treatment of safe waste in the field of their disposal and within the framework of implementation of EU legislation in Ukraine - Petrovych, O.; Yevsiukov, T. (Land Management, Cadastre and Land Monitoring, 2020)
Abstract. In Ukraine, the conceptual apparatus of municipal waste management in the field of their disposal has shortcomings, and in the framework of the implementation of EU legislation in Ukraine, new terms appear, which make their adjustments. This leads to uncertainty, ambiguity, discrepancy and misuse of concepts by waste actors, scientists, authors and more. To begin reforming the waste system, it is necessary to clarify the shortcomings of the past conceptual framework and clearly form an understanding of the new. This study is designed to analyze the conceptual apparatus of safe waste management in the field of disposal and in the implementation of EU legislation in Ukraine, namely the terminology before and after waste management reform, finding common and divergent, identifying shortcomings in interpretations and own vision of such definitions. In writing this article used a theoretical method, a method of studying regulatory and instructional documents, synthesis, analysis, comparison, grouping. The theoretical basis was the work of Ukrainian scientists, graduate students, the regulatory framework of Ukraine and the EU in the field of waste. At the end of the study, four groups of terms were formed, each of which clarifies the pros and cons of defining the terms, as well as suggested ways to improve the conceptual framework for safe waste in the field of disposal and implementation of EU legislation in Ukraine. Keywords. Conceptual apparatus, term, waste, landfill, implementation of EU legislation.